Windows Azure cloud platform - D. M. Reheta (CTE Workshop Proceedings, 2013)
The functions and design of adaptive information-computing networks concentrates on the concept of electronic data processing based on cloud computing information technology using the Windows Azure platform. This platform is based on running a virtual machine for each instance of an interactive application. According to this concept, networked virtual objects are formed thanks to a special user interface supported by the system programs by means of network configuration tools. These are network virtual sites as a situational component of a logical network infrastructure. Windows Azure sells two cloud models in full: Platform as a Service (PaaS) and Infrastructure as a Service (IaaS).